Association between mitochondrial DNA levels and depression: a systematic review and meta-analysis - Wenhui Li; Lingqun Zhu; Yi Chen; Yudi Zhuo; Shurun Wan; Rongjuan Guo (BMC Psychiatry, 2023)
Abstract Background Mitochondrial dysfunction leading to disturbances in energy metabolism has emerged as one of the risk factors in the pathogenesis of depression. Numerous studies have identified alterations in the content of mitochondrial DNA (mtDNA) in peripheral blood and cerebrospinal fluid of individuals with depression. Researchers have sought to establish a clear association between mtDNA and depression. Consequently, we conducted a comprehensive meta-analysis to assess the existing evidence regarding the impact of mtDNA on depression. Methods This study conducted a thorough search of the following databases up to March 13, 2023: PubMed, Embase, the Cochrane Library, the Web of Science, Wanfang Database, SINOMED, the China Science and Technology Journal Database, and China National Knowledge Infrastructure. The meta-analysis was carried out using RevMan (version 5.4) and Stata (version 16.0) software. In addition, publication bias was assessed with funnel plots, Begg’s test and Egger’s test. Results Our analysis included data from 10 articles, including 12 studies for further examination. A total of 1400 participants were included in this study, comprising 709 (including 300 males and 409 females) patients with depression and 691 (including 303 males and 388 females) healthy controls. The average age of depressed patients was (42.98 ± 2.55) years, and the average age of healthy people was (41.71 ± 2.6) years. The scales used to assess outcomes are Hamilton-rating scale for Depression(4 articles), Montgomery-Asberg Depression Rating Scale(3 articles), and Mini-Internatioal Neuropsychiatric Interview (1 articles). The meta-analysis revealed significantly higher levels of mtDNA in circulating blood samples and skin fibroblasts of individuals with depression in comparison to healthy controls [standardized mean difference(SMD) = 0.42, 95% confidence intervals(CI): 0.16, 0.67]. Conclusions Our study concludes that there is a significant (p < 0.05) increase in mtDNA levels in serum, plasma, and cerebrospinal fluid in individuals with depression. These findings suggest that mtDNA could serve as a potential biomarker for diagnosing depression. Registration number PROSPERO CRD42023414285.